2014
DOI: 10.2807/1560-7917.es2014.19.20.20806
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccination coverage and adherence to recommended age among infants in Flanders (Belgium) in 2012

Abstract: In Belgium, rotavirus vaccination has been recommended and partially reimbursed since October 2006. Through a retrospective survey in 2012, we estimated the coverage rate of the rotavirus vaccination in Flanders among infants born in 2010. Using a standardised questionnaire, 874 families were interviewed at home, collecting information on demographic characteristics, socio-economic background and documented vaccination history (updated from medical files and vaccination database, if needed). Adherence to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 17 publications
(19 reference statements)
4
28
3
5
Order By: Relevance
“…The study results revealed slightly lower percentage as compared to target statistics by Ndola District Health Management Office [15] obtained on uptake coverage of 85%. In addition, the study results were also lower as compared to study conducted by [10] in Anglia and Essex which revealed 90% -92% coverage and study of [11] in Flanders, Belgium which was at 92.2% as well as the earlier study [12] in Congo which revealed 99% uptake of rotavirus vaccine among under-five children.…”
Section: Discussion and Interpretation Of Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…The study results revealed slightly lower percentage as compared to target statistics by Ndola District Health Management Office [15] obtained on uptake coverage of 85%. In addition, the study results were also lower as compared to study conducted by [10] in Anglia and Essex which revealed 90% -92% coverage and study of [11] in Flanders, Belgium which was at 92.2% as well as the earlier study [12] in Congo which revealed 99% uptake of rotavirus vaccine among under-five children.…”
Section: Discussion and Interpretation Of Resultscontrasting
confidence: 78%
“…Other studies conducted by Braeckman [11] in Flanders, Belgium revealed uptake of rotavirus vaccine among under-five children to be at 92.2% where as those of Merten [12] in Congo revealed 99%.…”
Section: Introductionmentioning
confidence: 97%
“…22 This high vaccine uptake is maintained throughout subsequent years where parents are asked for a co-payment of the vaccine of 11.6€ per dose. 23 We have previously investigated the change in winter pediatric hospitalizations from before to after the introduction of rotavirus vaccination. 22 By reducing the seasonal influx of urgent RVGE cases into pediatric hospitals, the vaccine could help to reduce the winter pressure on healthcare resources and staff, offering potential wider benefits beyond reduced healthcare costs and quality-of-life gains in improving hospital quality of care (QoC).…”
Section: Introductionmentioning
confidence: 99%
“…These data also provide some insight into the extent to which the two different RV vaccine brands are used, and show that Rotarix has consistently continued to achieve the large majority of the RV vaccine market share in Belgium since it began to be routinely used in 2006. While routine national RV vaccine coverage data for Belgium are not yet available, RV vaccine coverage was estimated to be 92·2% (95% CI 90·2–93·8) in 2012 in a study conducted in the Flemish region alone [14]. In 2010 the Flemish region was estimated to contain ~58% of the total Belgian population [13] and the RV vaccine coverage estimate reflects the conclusions for RV vaccine uptake drawn from this analysis using IMS health sales data.…”
Section: Discussionmentioning
confidence: 79%